PANDANGAN HUKUM KESEHATAN TERHADAP ABORTUS PROVOCATUS BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 - Rumelda Silalahi; Rasmita Luciana (Jurnal Darma Agung, 2019)
Nowadays Abortion is a problem that often arises and has increased from year to year. Abortion is considered by most people as an act of murder, because the fetus or baby in the womb of a mother has the right to a reasonable life, and in any religion it is not permissible for a pregnant woman to stop her pregnancy for any reason. The main reasons for abortion are non-medical reasons including not wanting to have children for fear of interfering with career, school or other responsibilities, not having enough money to care for children, and not wanting to bear children without fathers. Another reason often cited is still too young (especially those who are pregnant out of wedlock), and can be a disgrace to the family. Reasons like this are also given by women in Indonesia who try to convince themselves that killing the fetus in the womb is permissible and justified. These reasons are definitely show the picture of irresponsibility woman in saving her life by sacrifice the life of her own baby. This study uses a normative method, which is to conduct an analysis of the problem and research through an approach in legislation and also sourced from books, papers, laws and other references. As for the problems in this study are first, the view of the health law against Provocatus Abortion based on Law Number 36 Year 2009, secondly the factors causing the occurrence of the Provocatus Abortion crime in society and the third is the criminal liability against the Provocatus Abortion Crime. The provisions of Law No. 23 of 1992 concerning Health, emphasizing the permissibility to carry out acts of abortion in an effort to save the life of the mother and / or fetus, this type of abortion is legally justified and protected by law and with medical considerations.